(untitled) (Journal of Science and Technology, 2016)
The silica and nitrogen contents rf the dry weights of five maize varieties Obatanapa, Abelechi, Okomasa, Ewifompe and Abutui were determined using the gravimetric method and Kjedahl’s method respectively to determine how the affect the level of stemborer infestation in maize. The experiment was conducted in the major and minor planting seasons. In the minor season, the silica content of the stem ranged from 0.44% dry weight in Obatanpa to 0.53% In Abutui. The difference; were statistically not significant (I’ 5 0.051. Higher percent silica was recorded for the different maize varieties in the major season. This ranged from 1.19% in Abelechi to 1. in in Ahura/. The differences in the percent silica was statistically not significant (P > 0.05). There was a high negative correlation between the percent silica and the number of infested plants as well as the number of larvae/pupae per infested plant. In the minor season the nitrogen content ranged from 0.151% In Abutui to 26.1% in Ewifompe whilst in the major season it ranged from 0.40% in Ahutui to 0.90% in Ewifompe. Stem borer infestation appeared to correlate Ix-0h nitrogen content of the stem